2018
DOI: 10.1007/s10661-018-6569-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of textile industry effluent with mutagenicity and its toxic health implications upon acute and sub-chronic exposure

Abstract: Complex industrial discharges pose certain risks to the ecosystem. This study was aimed at identifying acute and sub-chronic toxicological effects of the textile industry wastewater. The textile wastewater was evaluated for the metals and organic pollutants by atomic absorption spectrophotometer and GC-MS respectively. In vitro genotoxicity and mutagenicity were assessed by Comet assay in peripheral lymphocytes isolated from Ovis aries and Ames test in Salmonella typhimurium strains TA-100 and 102 respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Previously, it was found that catechin, epicatechin, chlorogenic acid, gallic acid and mangiferin were responsible for decreasing hyperlipidemia in diabetic animals. A lipid lowering activity of the plant extract may be associated with the presence of these phytochemicals [7,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was found that catechin, epicatechin, chlorogenic acid, gallic acid and mangiferin were responsible for decreasing hyperlipidemia in diabetic animals. A lipid lowering activity of the plant extract may be associated with the presence of these phytochemicals [7,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were dissected to remove the liver, kidney and pancreas, and preserved in 10% formalin. Tissues were embedded in paraffin wax and their 5 µm sections were prepared with microtome followed by staining with Hematoxylin and eosin (Akhtar et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The liver, kidney, lung, and heart from three of the five animals were stored in 10% neutral buffered formalin for histopathological examination. The tissues embedded in paraffin wax were sectioned (3‐5 µm) with a microtome (Model: HS‐3345, Zeedo, Jinhua Hisure Scientific, Co; LTD China), mounted on slides, and stained with H&E for observation under photomicroscope (Akhtar et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The organs were observed carefully for any gross toxicity signs including lesions and altered organ size or color. Thereafter, kidney, liver, lung, and heart isolated from three animals per group were stored in 10% neutral buffered formalin for histological examination as described previously (Akhtar et al., 2018).…”
Section: Methodsmentioning
confidence: 99%